2021
DOI: 10.1093/brain/awab245
|View full text |Cite
|
Sign up to set email alerts
|

GPR151 in nociceptors modulates neuropathic pain via regulating P2X3 function and microglial activation

Abstract: Neuropathic pain is a major health problem that affects up to 7–10% of the population worldwide. Currently, neuropathic pain is difficult to treat due to its elusive mechanisms. Here we report that orphan G protein-coupled receptor 151 (GPR151) in nociceptive sensory neurons controls neuropathic pain induced by nerve injury. GPR151 was mainly expressed in nonpeptidergic C-fiber dorsal root ganglion (DRG) neurons and highly upregulated after nerve injury. Importantly, conditional knockout of Gpr151 in adult noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 87 publications
0
26
0
Order By: Relevance
“…Mechanistically, GPR151 seems to interact with the purinergic receptor P2X3 in sensory neurons. As a consequence, the activity of P2X3 increases causing enhanced activity of sensory neurons and subsequent activation of spinal microglia under neuropathic pain conditions [137].…”
Section: Proton-sensing Gpcrs In Persistent Pain Statesmentioning
confidence: 99%
“…Mechanistically, GPR151 seems to interact with the purinergic receptor P2X3 in sensory neurons. As a consequence, the activity of P2X3 increases causing enhanced activity of sensory neurons and subsequent activation of spinal microglia under neuropathic pain conditions [137].…”
Section: Proton-sensing Gpcrs In Persistent Pain Statesmentioning
confidence: 99%
“…In addition, P2X 3 and P2X 7 receptors have been found to be regulated by lncRNAs ( Seino et al, 2006 ; Peng H. et al, 2017 ). The two receptors play a role in the development of chronic pain ( Wu et al, 2021 ; Xia et al, 2021 ). Furthermore, the levels of pro-inflammatory factors, such as IL-1β, IL-6, IL-12, and TNF-α ( Xia et al, 2018 ; Li Z. et al, 2020 ; Pan et al, 2020 ), have been found to change in chronic pain after lncRNA downregulation.…”
Section: The Role Of Lncrnas In the Nervous System And The Pain-signaling Pathwaymentioning
confidence: 99%
“…Western blot analysis results suggested that the Gm14461 knockdown could downregulate the expression of CGRP and P2X 3 / 7 receptors at the protein level in TN mice. The three proteins are reported to participate in the development of neuropathic pain ( Hansen et al, 2016 ; Wu et al, 2021 ; Xia et al, 2021 ). Moreover, Gm14461 upregulates the expression of TNF-α, IL-1β, and IL-6 ( Xu et al, 2020 ).…”
Section: Lncrnas and Chronic Neuropathic Painmentioning
confidence: 99%
“…CXCR3 is a key player in the pathophysiological process of many inflammatory conditions and associated to pain modulation in DRG and spinal cord [ 67 ]. GPR151 has been associated to DRG hyperexcitability in neuropathic chronic pain [ 68 ]. Methylation changes are not specific to neuropathic pain, as different forms of chronic pain, like chronic inflammatory or visceral, were also accompanied by different methylation states [ 69 , 70 , 71 ].…”
Section: Epigenetic Mechanisms In Chronic Painmentioning
confidence: 99%